The analysis of the factors influencing the awareness of post-operative neurosurgery patients in the ICU of a hospital - N.C Sitanggang, Margaretha; Karnirius Harefa; Tati Murni Karo Karo (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: The Intensive Care Unit (ICU) plays a crucial role in the care of post-surgical neurosurgery patients, as patients with critical conditions require close monitoring. The changes in the consciousness level of post-neurosurgery patients are influenced by various factors, including age, gender, Glasgow Coma Scale (GCS), family support, and teamwork among medical staff. Objective: This study aims to analyze the factors influencing the changes in the consciousness level of post-neurosurgery patients in the ICU of Grandmed Lubuk Pakam Hospital in 2024. Research Method: This study uses a cross-sectional design with primary data collection through observation and direct measurement. The sample consists of 40 post-surgical neurosurgery patients treated in the ICU of Grandmed Lubuk Pakam Hospital. Data were analyzed using univariate, bivariate, and multivariate analysis, employing chi-square tests and logistic regression. Results: The results show that factors such as age, gender, GCS, family support, and teamwork significantly influence the consciousness level of patients. The GCS factor (?8) has the most dominant effect, with an Odds Ratio (Exp(B)) = 5.523, indicating that patients with a low GCS have 5 times the risk of experiencing a decrease in consciousness compared to patients with a higher GCS. Conclusion: Factors such as age, gender, GCS, family support, and teamwork influence the changes in the consciousness level of post-neurosurgery patients. Monitoring GCS and strengthening teamwork, along with family support, can accelerate the recovery of patients' consciousness.